Religion and the internet: digital religion, (hyper)mediated spaces, and materiality - Evolvi, Giulia (Zeitschrift für Religion, Gesellschaft und Politik, 2022)
This article offers theoretical reflections on the study of religion and the Internet by critically discussing the notion of "digital religion" (Campbell 2012). In particular, it stresses the importance of integrating material and spatial approaches to the study of digital religion. In doing so, it proposes the theory of "hypermediated religious spaces" to describe processes of religious mediation between online and offline environments by taking into account materiality and space. The article discusses theoretical perspectives by means of case studies: first, the importance of materiality within Internet practices is illustrated through the example of Neo-Pagan online rituals; second, the notion of space, and "third space" in particular, in relation to Internet practices is analyzed through the case of the hashtag #Nous-Sommes-Unis, circulated by French Muslims; third, the theory of hypermediated spaces is exemplified by the analysis of a live-streamed mass in the Italian city of Manerbio during the Covid-19 lockdown. The article aims at kindling scholarly reflections on terminologies and theories for the global and interdisciplinary study of digital religion.